2022
DOI: 10.3390/ijms231911423
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Proteins at Excitatory Synapses in the Brain—Relationship with Depressive Disorders

Abstract: Depressive disorders (DDs) are an increasingly common health problem that affects all age groups. DDs pathogenesis is multifactorial. However, it was proven that stress is one of the most important environmental factors contributing to the development of these conditions. In recent years, there has been growing interest in the role of the glutamatergic system in the context of pharmacotherapy of DDs. Thus, it has become increasingly important to explore the functioning of excitatory synapses in pathogenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 209 publications
0
5
0
Order By: Relevance
“…The overexpression of PSD-95 in hippocampal neuronal cells enhances the maturation of glutamatergic synapses; therefore, PSD-95 plays a pivotal role in regulating synaptic maturation, indicating its involvement in stabilizing and modulating synaptic plasticity [ 67 ]. Several studies have shown that the disruption of PSD-95 in depression inhibits the production of nNOS-derived free radicals and reduces excitotoxicity by blocking the signaling of calcium-ion-activated N-methyl-D-aspartate receptors in the amygdala [ 68 , 69 ]. Furthermore, FRMPD3 is an NPAS4-regulated inhibitory neuronal gene, suggesting that the activity of FRMPD3 promotes the development of excitatory synaptic connections in somatostatin neurons [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of PSD-95 in hippocampal neuronal cells enhances the maturation of glutamatergic synapses; therefore, PSD-95 plays a pivotal role in regulating synaptic maturation, indicating its involvement in stabilizing and modulating synaptic plasticity [ 67 ]. Several studies have shown that the disruption of PSD-95 in depression inhibits the production of nNOS-derived free radicals and reduces excitotoxicity by blocking the signaling of calcium-ion-activated N-methyl-D-aspartate receptors in the amygdala [ 68 , 69 ]. Furthermore, FRMPD3 is an NPAS4-regulated inhibitory neuronal gene, suggesting that the activity of FRMPD3 promotes the development of excitatory synaptic connections in somatostatin neurons [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endowed with a remarkable variety of biological functions, NMDA receptors constitute heterotetrameric complexes composed of combinations of the subunits GluN1, which is processed in eight distinct splice variants, GluN2A-D, and GluN3A-B. Typically, a functional NMDA receptor comprises two glycine-binding GluN1 subunits and at least one glutamate-binding GluN2 subunit. Simultaneous binding of glycine and glutamate initiates NMDA receptor activation, which involves voltage-dependent relief of magnesium blockade, depolarization of the postsynaptic membrane, and calcium ion influx. While NMDA receptors are key players in neurophysiology, contributing to memory and learning via modulation of synaptic plasticity, the GluN2B subunit-carrying NMDA receptor has been implicated in the pathophysiology of various neurological disorders. Indeed, the role of overstimulation of the excitatory GluN2B subunit in the development of several CNS-related pathologies has been corroborated, , whereas targeting GluN2B-mediated excitotoxicity has been suggested as a promising therapeutic strategy for various diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), ischemic stroke, traumatic brain injury, neuropathic pain, and depression. Early efforts to develop NMDA receptor antagonists prompted the discovery of NMDA receptor open channel blockers such as phencyclidine (PCP), thienylcyclohexylpiperidine (TCP), ketamine, memantine, and MK-801 (dizocilpine). Despite their well-documented therapeutic efficacy, most of these “broad-spectrum” antagonists were associated with a poor safety profile, potentially owing to the lack of subunit-selectivity. ,, As such, more recent attempts have focused on the development of GluN2B-selective antagonists, which has become feasible since the discovery of the N- terminal domain (NTD) binding site that is located at the interface between the GluN1 and GluN2B subunit .…”
Section: Introductionmentioning
confidence: 99%
“…8 This overactivation of NMDA receptors and concomitant excitotoxicity plays a key role in the development of various pathologies including depression, ischemic stroke, neuropathic pain, traumatic brain injury and neurodegenerative disorders such as Alzheimer's disease, Parkinson's disease and multiple sclerosis. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Therefore, the development of antagonists or negative allosteric modulators of the NMDA receptor inhibiting the influx of Ca 2+ ions into the neuron is of particular interest.…”
Section: Introductionmentioning
confidence: 99%